Kinetics of Complex Plasmas - Sodha, Mahendra Singh (Springer Series on Atomic, Optical, and Plasma Physics, 2014)
The presentation in the book is based on charge balance on the dust particles, number and energy balance of the constituents and atom-ion-electron interaction in the gaseous plasma. Size distribution of dust particles, statistical mechanics, Quantum effects in electron emission from and accretion on dust particles and nonlinear interaction of complex plasmas with electric and electromagnetic fields have been discussed in the book. The book introduces the reader to basic concepts and typical applications. The book should be of use to researchers, engineers and graduate students.